Change in diagnostic confidence brought about by using in utero MRI for fetal structural brain pathology: analysis of the MERIDIAN cohort. Issue 6 (June 2017) - Griffiths, P.D.; Bradburn, M.; Campbell, M.J.; Connolly, D.J.A.; Cooper, C.L.; Jarvis, D.; Kilby, M.D.; Mason, G.; Mooney, C.; Robson, S.C.; Wailoo, A.; ,
Abstract : Aim: To measure possible change in diagnostic confidence by performing in utero magnetic resonance imaging (iuMRI) studies on fetuses with brain abnormalities recognised on ultrasonography (US). Materials and methods: The analyses are based on the primary cohort from the prospective MERIDIAN study, which consisted of 570 fetuses with brain abnormalities detected on US, with iuMRI performed within 2 weeks of US and complete outcome reference data. The cohort was recruited between July 2011 and August 2014, and written informed consent was obtained for all participants. They all had indicators of diagnostic confidence measured on US by fetal medicine experts and iuMRI by the reporting radiologists. Three assessments were carried out using the conventional uncorrected (C2 –C1 %) method, the conventional (C2 –C1 %) with the Omary correction, and the score-based weighted average method. Results: All three assessments showed statistically significant ( p <0·0001) positive effects indicating that iuMRI was potentially beneficial when included in the diagnostic pathway for prenatal structural brain anomalies (in terms of diagnostic confidence). Conclusion: These results strongly support the routine clinical use of iuMRI as an adjunct to US when assessing fetuses with structural brain abnormalities. Highlights: The MERIDIAN study showed that iuMR imaging improves the diagnostic accuracy of detecting fetal brain abnormalities. We describe three methods of assessing changes in diagnostic confidence as a result of iuMR imaging. All three methods show statistically significant improvements over prenatal ultrasonography alone.